Defining the Salvage Time Window for the Use of Ischemic Postconditioning in Skeletal Muscle Ischemia Reperfusion Injury - Schmucker, Ryan W.; Mendenhall, Shaun D.; Reichensperger, Joel D.; Yang, Mei; Neumeister, Michael W. (Journal of Reconstructive Microsurgery, 2015)
Background The aim of this study was to determine the optimal salvage time window within which ischemic postconditioning can be used to ameliorate ischemia/reperfusion (I/R) injury in skeletal muscle.Methods A total of 48 Sprague–Dawley rats were divided into two groups: I/R only (control) and I/R with postconditioning. Subgroups were divided by duration of ischemia (2, 4, 6, and 8 hours). A pedicled gracilis muscle model was used. The postconditioning protocol consisted of six cycles of 15 seconds of reperfusion followed by 15 seconds of ischemia (total time = 3 minutes). Muscles were harvested 24 hours after I/R injury to examine tissue viability, histology, myeloperoxidase activity, and protective gene expression.Results Postconditioning groups showed improved muscle viability after 4 and 6 hours of ischemia time as compared with controls (p < 0.05). Higher expression of mitochondrial complexes I, II, III, endothelial nitric oxide synthase, inducible nitric oxide synthase, and Bcl-2 were observed in the postconditioning group after 4 and 6 hours of ischemia (p < 0.05). Lower expression of tumor necrosis factor-α and caspase 3 was observed in the postconditioning group at 4 hours (p < 0.05). Myeloperoxidase activity was similar in both groups at all-time points except 8 hours ischemia, where the control group had higher activity (p < 0.05).Conclusion Results of this study demonstrate that the effective time window within which postconditioning is most effective for the salvage of skeletal muscle is between 4 and 6 hours of ischemia. Postconditioning offered improved mitochondrial and vascular function with decreased inflammation and cell death. This may be clinically useful as a postinjury salvage technique to attenuate I/R injury after 4 to 6 hours of ischemia.
Keywords: ischemia-reperfusion injury; ischemic postconditioning; skeletal muscle; replantation; free tissue transfer; salvage time window